Efficiency of Urban Wetlands in Removing Agricultural Non-point Source Pollution - Ren, Y.B.; Ren, N.Q.; Li, X.K.; Li, J.G. (Asian Journal of Chemistry, 2013)
In this study, field monitoring together with laboratory analysis were conducted to investigate the efficiency of urban wetlands in removing agricultural non-point source pollution. The urban wetland and two neighboring farmland in Wanbao County, Songbei district, Harbin city of China was selected as target field and seasonal variation of the agricultural non-point source pollution in wetland water body and agricultural runoff was also determined. Results showed that the concentration of the agricultural non-point source pollutants in the water body of wetland decreased substantially after purification by the wetland, which was lower than that in the farmland runoff. The concentrations of total nitrogen, NO3-N, NH4+-N and total phosphorus decreased by 74.22, 50.38, 77.94 and 17.91 % respectively, indicating that urban wetlands can intercept and remove agricultural non-point source pollutants effectively. In seasonal changes, total nitrogen and NO3-N concentration increased first and then decreased reaching the highest value in May; the concentrations of NH4+-N reached the highest value in October; the highest total phosphorus concentration was found in August.